Comparison of the Trilogy of Imam Ath-Thabarānī's Works: Al-Mu'jam Al-Kabīr, Al-Mu'jam Ash-Shaghīr and Al-Mu'jam Al-Awsath (Analysis of Compilation Methodology) - Rakhmat Fitrah Ramdhani; Milzam Priambodo; Rizzaldy Satria Wiwaha; Dadah; Mohamad Anton Athoillah (al-Afkar, Journal For Islamic Studies, 2026)
This paper analyzes the trilogy of mu'jam by Imam Abū al-Qāsim Sulaimān bin Aḥmad ath-Thabarānī (260–360 H): Al-Mu'jam al-Kabīr, Al-Mu'jam al-Awsath, and Al-Mu'jam ash-Shaghīr. This study uses a library method and a hadith science approach through a comparison of primary sources of study, namely the three ath-Thabarānī trilogies as canonical sources of hadith that complement the treasury of hadith science, then supported by various books related to hadith science as secondary sources of research. The focus of the study includes the methodology of compilation, the character of the curation of the narration, and the comparative value of the three for hadith studies—especially access to sanad verification and mapping of transmission paths which aim to understand the contents of each Mu’jam and analyze its function and contribution to sanad verification and path studies. Methodologically, al-Kabīr is arranged according to the musnad of the companions alphabetically (starting with Khulafā' Rāshidīn, then 'asyarah al-mubashsharūn), thus facilitating the consolidation of all narrations per companion. Al-Awsath is organized by the names of the teachers (shuyūkh) of Thabarānī and functions as a "bank of unique/gharīb" traditions, often accompanied by 'ilal commentary on the uniqueness of the lines. ash-Shaghīr is also based on shuyūkh; its primary purpose is to catalog teachers—generally one hadith per teacher—with a brief biographical introduction. The comparison reveals three layers of function: (1) al-Kabīr as a comprehensive "data lake"; (2) al-Awsath as a complement of perspectives through gharā'ib; (3) ash-Shaghīr as a practical index of transmission networks. The contemporary relevance of this study, as concluded, is evident in the ease of replicating the mu'jam model for digital databases—searching by companion/teacher, auditing lines, and tiered curation for teaching and research. Thus, this trilogy provides a rich framework for sanad criticism and ethical development through the expansion of the corpus of pedagogically and academically valuable traditions.